THE EVOLUTION OF STRATEGIC MANAGEMENT IN PLATFORM-BASED BUSINESS MODELS: THE CASE OF UBER AND AIRBNB - Ma. Yuzhen (Modern American Journals, 2025)
The rise of platform-based business models has revolutionized strategic management across various industries. Companies like Uber and Airbnb exemplify how digital platforms can disrupt traditional markets, create new value chains, and redefine consumer behavior. This paper examines the evolution of strategic management in platform businesses, focusing on Uber and Airbnb as case studies. It analyzes the strategic shifts from asset ownership to network orchestration, customer co-creation, and data-driven optimization. The study highlights how these companies manage scalability, governance, competition, and regulation through innovative strategies, offering insights for future platform ventures.
Keywords: Platform economy, digital platforms, strategic management, Uber, Airbnb, network effects, business model innovation, sharing economy, digital disruption, platform governance